Revisiting the mismatch between formal education in computer science and the software and information services sector: the case of Argentina. (1st June 2014) - Zukerfeld, Mariano
Abstract : The Argentinean software and information services (SIS) sector has grown steadily over the last decade. However, academics, policy makers and managers agree that the shortage of computer science (CS) degree-holders has been (and is) jeopardizing future growth. This paper depicts the situation of formal education in CS and related areas in Argentina, providing the necessary basis from which to call into question the assumption that the primary driving force of a powerful SIS sector is CS graduates. After presenting figures of enrollment, graduates and researchers, we find that while it is true that there is a mismatch between the trends of formal education in CS and that of Argentinean SIS, it is not clear at all that the sector is limited because of that. First, international comparisons with the US and the UK show that the proportion of graduates is not necessarily the main driver of a highly innovative SIS sector. Secondly, qualitative sources underline the relevance of informal learning in the acquisition of the software skills actually used by workers. Additionally, the particular evolution of SIS wages could be limiting the inflow of graduates into the sector.